Fatty Infiltration of the Myocardium and Arrhythmogenesis: Potential Cellular and Molecular Mechanisms - Anumonwo, Justus M. B.; Herron, Todd (Frontiers in Physiology, 2018)
Anatomical evidence in several species shows highly heterogeneous fat distribution in the atrial and ventricular myocardium. Atrial appendages have fat deposits, and more so at the posterior left atrium. Although such fat distributions are considered normal, fatty infiltration is regarded arrhythmogenic, and various cardiac pathophysiological conditions show excess myocardial fat deposits, especially in the epicardium. Hypotheses have been presented for the physiological and pathophysiological roles of epicardial fat, however this issue is poorly understood. Therefore, this mini-review will focus on epicardial fat distribution and the (patho)-physiological implications of this distribution. Potential molecular mechanisms that may drive structural and electrical myocardial remodeling attendant to fatty infiltration of the heart are also reviewed.